Erratum to: Search for the HH → bb[bar]bb[bar] process via vector-boson fusion production using proton-proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Kugel, Andreas; Napolitano, Fabrizio; Ott, Philipp; Schöning, André; Schultz-Coulon, Hans-Christian; Spieker, Thomas; Stamen, Rainer; et al. (Journal of high energy physics, 2021)
One correction is noted for the paper. A wrong cross-section was used for the theory prediction in figure 6 due to not taking into account the VHH contamination properly in the rescaling formula for the signal samples.
The ATLAS collaboration: G. Aad, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, A. Kugel, F. Napolitano, P. Ott, A. Schoening, H.-C. Schultz-Coulon, T. Speker, R. Stamen, P. Starovoitov, L. Vigani, S. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 11.03.2021
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel steht jeweils der zweite Buchstabe b mit einem Oberstrich